A Framework for Design Patterns in TROPOS - Do, T. Tung; Kolp, Manuel; Hoang, T. T. Hang; Pirotte, Alain (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2003)
Multi-Agent Systems (MAS) architectures are gaining popularity over traditional ones for building open, distributed, and evolving software. Since the fundamental concepts of multiagent systems are social and intentional rather than object, functional, or implementationoriented, the design of MAS architectures should be eased by using what we call social patterns rather than object-oriented design patterns. Social patterns are idioms inspired by social and intentional characteristics used to design the details of a system architecture. The paper presents a framework called SKWYRL used to gain insight into social patterns and help design a MAS architecture in terms of these new idioms. The framework is integrated in the TROPOS agent methodology. It is developed according to the five modeling dimensions provided by TROPOS: social, intentional, structural, communicational, and dynamic. We consider the Broker social pattern as a combination of patterns and use it to illustrate the modeling dimensions of SKWYRL. A framework for code generation is also presented as well as an e-business broker module.